Development and validation of the Quran – Science, Technology, Engineering, Art, And Mathematics (Q-STEAM) module - Muzakkir; Rose Amnah Abd Rauf; Hutkemri Zulnaidi (STEM Education)
This study evaluates the content validity of the Quran-science, technology, engineering, art, and mathematics (Q-STEAM) module, designed to integrate Quranic approach with STEAM (Science, Technology, Engineering, Art, and Mathematics) education. This integration aims to enhance mathematics understanding while fostering Islamic character. The integration of the Quran in this module is dominated by mathematics to deliver the Quran and mathematics with the Quran. The module was designed using Borg and Gall's research method. Ten experts, who are specialists in the domains of mathematics education, STEAM education, Islamic education, and Indonesian language, assessed the module. The assessment resulted in high validity scores, where the results indicated that the content validity index for the Q-STEAM module falls within the range of 83–100%. The instrument used in this research is the content validity form. The experts agreed that the contextual problem should be set at the beginning of the module so that the contextualization of learning can be realized and that learners should be familiarized with triggering questions to stimulate thinking and recall concepts that have been learned. Similarly, the experts explained that the module should be structured according to the students' developmental trajectories to help students understand the context. This module has designed learning that integrates Quranic verses in every engineering design process (EDP) step in completing the project. This module can be used as a reference in professional development training for teachers in courses for mathematics education.